Powerpoint and Wondershare Quiz Creator Interactive Multimedia Development to Improve Student Learning Motivation - Maulida Maulida; Gimin Gimin; Sri Kartikowati (Universitas Riau, 2019)
Low learning motivation of the student sometime it is due to the teacher has difficulty choosing the right learning media. This study was to produce powerpoint-based accounting and wondershare quiz creator multimedia to improve student learning motivation. Data collection begins with the need analysis phase. The media was validated interm of its interactive and content by the validators. The result the validator 1 and 2 obtained a score of 75 in the feasible category and the material feasibility by material expert obtained a score of 59 and 66 in the feasible category. Furthermore, the small scale test was showing that the media is useful to be used because it reaches a minimum score of> 37.5 - 48.78 (High category). The results of the analysis show that there are differences in the level of student motivation in the experimental class in the category of High of 62.5% and student motivation in the control class is in the Low category of 59.4%. Based on the results, the developed media is possible to use in the real teaching class.